The position of Vang church, alias Wang Temple (Karpacz, Poland), in Norwegian stave church literature - Lange, Tadeusz W. (Wydawnictwo Naukowe UAM, 1992)
The author presents shortly the history of Vang stave church from Valdres, now situated in Karpacz (Poland), the only Norwegian stave church to be found outside the Norwegian borders. The aim of the paper has been to examine critically the place of Vang church in stave church literature over the last 150 years. The paper also includes a complete bibliography of the church.